Preparation method and application of multifunctional wet adhesive
Patent Information
- Application Number
- CN202311404035.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-10-27
AI Technical Summary
[0005]为了解决传统湿性黏合剂的缺点,本发明提供了一种多功能湿性黏合剂及其制备方法
[0022](1)本发明以通过简单的“一锅法”合成方式制备了多功能湿性黏合剂,方法简单,操作方便,价格低廉,可重复利用,不需要很高的技术要求,且易对黏合剂的机械性能、黏附性能、抗氧化性能进行调控。
Smart Images

Figure CN117427206B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomaterials, specifically relating to a method for preparing a multifunctional wet adhesive, which can be applied in technical fields such as promoting wound healing. Background Technology
[0002] In recent years, tissue adhesives have received widespread attention from scientists as a good alternative to surgical sutures in wound repair. However, most commercially available tissue adhesives currently suffer from poor biocompatibility, slow adhesion formation, and poor mechanical compatibility with tissues. To address these challenges, scientists have developed many hydrogel-based wet adhesives inspired by mussels. The catechol groups in mussel adhesive proteins can interact with the target interface through hydrogen bonding, coordination, and π-π stacking. However, these catechol-based hydrogel adhesives are typically synthesized through oxidative polymerization, exhibiting significant instability. Uncontrolled oxidation processes lead to a reduction in phenolic hydroxyl groups, thereby decreasing adhesive strength.
[0003] Furthermore, the vast majority of hydrogels are designed by grafting molecules with catechol structures onto biocompatible macromolecules such as chitosan, hyaluronic acid, and polyethylene glycol. The preparation of these hydrogels relies on complex designs and expensive reagents, which is not only time-consuming but also costly, limiting large-scale production. Therefore, it is urgent to develop simple and economical wet adhesives that exhibit stable adhesion, excellent mechanical properties, good biocompatibility, and strong adaptability.
[0004] Given that mussels can achieve antioxidant effects through acidification mechanisms and thiol-mediated redox regulation, thus exhibiting strong wet adhesion, we added quaternized chitosan as an antioxidant to the acidic environment generated by acrylic acid to simulate the antioxidant environment of mussels. Furthermore, we combined it with polydopamine rich in catecholamine structures. Therefore, in this invention, we developed a multifunctional wet adhesive through a simple one-pot synthesis method and investigated its practical effects on wound healing. Summary of the Invention
[0005] To address the shortcomings of traditional wet adhesives, this invention provides a multifunctional wet adhesive and its preparation method.
[0006] Technical solution: To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0007] A multifunctional wet adhesive and its preparation method are provided. The multifunctional wet adhesive is characterized by adjustable mechanical properties, adhesive properties and antioxidant properties.
[0008] A method for preparing a multifunctional wet adhesive includes: dissolving dopamine hydrochloride powder in Tris-HCl buffer for prepolymerization to form a polydopamine solution, followed by freeze-drying to obtain polydopamine powder; adding quaternized chitosan powder to an acrylic acid solution to construct an acidic and antioxidant solution, and then adding the prepared polydopamine powder to this solution; after stirring evenly, adding an initiator to the pregel solution, stirring to form a homogeneous solution, pouring the solution into a mold, and allowing it to stand in a sealed environment until it naturally cures to obtain the multifunctional wet adhesive.
[0009] As a preferred embodiment of the present invention, the preparation method of the multifunctional wet adhesive includes the following steps:
[0010] (1) Dopamine hydrochloride powder was dissolved in Tris-HCl buffer, stirred at 20-28℃ in a dry environment, and freeze-dried to obtain polydopamine powder.
[0011] (2) The quaternized chitosan powder is uniformly dispersed in an acrylic acid solution, and the entire solution is acidified by the carboxyl groups of acrylic acid. The quaternized chitosan serves as an antioxidant component in the solution.
[0012] (3) Disperse the polydopamine powder prepared in step (1) into the solution prepared in step (2) and stir at room temperature for 2-5 hours;
[0013] (4) Add ammonium persulfate powder to the solution prepared in step (3), then quickly add tetramethylethylenediamine, stir vigorously until all components are completely dissolved, stop stirring, seal the solution, and let it stand at room temperature for 1-3 hours to obtain a wet adhesive.
[0014] As a preferred embodiment of the present invention, the dopamine prepolymerization reaction is carried out at a temperature of 25°C for a time of 60 minutes.
[0015] As a preferred embodiment of the present invention, the final concentration of the quaternized chitosan solution in the acrylic acid solution is 1-5% (w / v), preferably 3% (w / v), and the concentration of acrylic acid is 28-35% (w / v), preferably 30% (w / v).
[0016] As a preferred embodiment of the present invention, the concentration of polydopamine is 0.2-2 mg / mL, more preferably 0.4 mg / mL.
[0017] As a preferred embodiment of the present invention, the final concentration of ammonium persulfate in the solution is 2-5% (w / v), preferably 3% (w / v); and the final concentration of tetramethylethylenediamine in the solution is 1-4% (v / v), preferably 2% (v / v).
[0018] This invention discloses a method for preparing a multifunctional wet adhesive, wherein the wet adhesive can achieve different mechanical properties by adjusting the polydopamine content. By appropriately increasing the polydopamine content, the crosslinking density of the hydrogel increases, and its mechanical strength also increases. However, when the polydopamine content is excessively increased, it will affect the polymerization of the hydrogel, leading to a decrease in mechanical strength and causing the hydrogel to exhibit shear-thinning properties.
[0019] The method for preparing a multifunctional wet adhesive describes a wet adhesive whose adhesive properties can be obtained by adjusting the polydopamine content. By appropriately increasing the polydopamine content, the adhesive properties of the wet adhesive increase. However, when the polydopamine content is excessively increased, the adhesive properties of the wet adhesive no longer increase but instead begin to decrease.
[0020] The method for preparing a multifunctional wet adhesive describes a wet adhesive whose antioxidant properties can be obtained by adjusting the polydopamine content. Increasing the polydopamine content increases the antioxidant properties of the wet adhesive.
[0021] Beneficial effects: Compared with existing solutions, the advantages of this invention are:
[0022] (1) The present invention prepares a multifunctional wet adhesive by a simple one-pot synthesis method. The method is simple, easy to operate, inexpensive, reusable, does not require high technical requirements, and the mechanical properties, adhesive properties and antioxidant properties of the adhesive can be easily controlled.
[0023] (2) The wet adhesive prepared by the present invention has good biocompatibility and good antibacterial, hemostatic and antioxidant functions, and can be used to promote wound repair. Attached Figure Description
[0024] Figure 1 Schematic diagram of the wet adhesive preparation process: Step (1) is the polymerization reaction of dopamine under the action of Tris-hydrochloric acid, which increases the molecular chain length; Step (2) is to mix acrylic acid and quaternized chitosan to construct an acidic and antioxidant solution environment; Step (3) is to add the polymerized dopamine to the solution in step (2); Step (4) is to add crosslinking agent and initiator to the solution to solidify the solution and form a gel. The gel network formed after the solution is solidified is shown in the figure on the right. Hydrogen bonds are widely formed between the polydopamine molecular chain and the acrylic acid and quaternized chitosan molecular chains, including the phenolic hydroxyl groups on the polydopamine molecular chain and the carboxyl groups on the acrylic acid chain, the phenolic hydroxyl groups on the polydopamine molecular chain forming hydrogen bonds with each other, the benzene rings on the polydopamine molecular chain forming Π-Π conjugation, and the carbonyl groups on the polydopamine molecular chain forming hydrogen bonds with the hydroxyl groups on the quaternized chitosan.
[0025] Figure 2A picture of a wet adhesive.
[0026] Figure 3 Mechanical strength of wet adhesives: Young's modulus test results of wet adhesives. Storage modulus of multifunctional wet adhesives prepared under different schemes: the storage modulus of multifunctional wet adhesives gradually increases with the increase of polydopamine concentration.
[0027] Figure 4 Shear-thinning properties of wet adhesives: viscosity-shear rate curves of wet adhesives. When the concentration of polydopamine introduced is 2 mg / mL, the multifunctional wet adhesive exhibits shear-thinning properties, and its viscosity gradually decreases with increasing shear rate.
[0028] Figure 5 Self-healing properties of wet adhesives: Cyclic stress-strain curves of wet adhesives. When the introduced polydopamine concentration is 2 mg / mL, the wet adhesive exhibits self-healing properties. When the strain is less than 100%, the storage modulus of the wet adhesive is greater than the loss modulus, exhibiting a solid state. When the strain is greater than 1000%, the loss modulus of the wet adhesive is greater than the storage modulus, exhibiting a liquid state. When the strain recovers from 1000% to 100%, the storage modulus of the wet adhesive recovers rapidly, indicating that it can recover from a liquid state to a solid state.
[0029] Figure 6 Adhesive strength of wet adhesives: The adhesive strength of wet adhesives was tested under an lap-shear test. When the concentration of introduced polydopamine is below 0.4 mg / mL, the adhesive strength of the wet adhesive increases with the increase of the amount of introduced polydopamine. When the concentration of introduced polydopamine exceeds 0.4 mg / mL, reaching 0.8 mg / mL and 2 mg / mL, the adhesive strength of the wet adhesive decreases instead of increasing.
[0030] Figure 7 Biocompatibility of wet adhesives: OD value analysis of wet adhesives co-cultured with cells for 1-3 days. During 24, 48, and 72 hours of co-culture with cells, the wet adhesives prepared under different protocols all exhibited cytotoxicity comparable to the control group, demonstrating good biocompatibility.
[0031] Figure 8 Antibacterial properties of wet adhesives: Results of bacterial live / dead staining fluorescence after co-culturing the wet adhesive with different bacteria for 24 hours. From top to bottom, the results show the live / dead staining of *Escherichia coli*, *Staphylococcus aureus*, and *Pseudomonas aeruginosa*. From left to right, the results show the control group and the wet adhesive group. The wet adhesive exhibits excellent antibacterial properties.
[0032] Figure 9Hemostatic properties of wet adhesives: Figure a shows the physical images of rat liver laceration bleeding models after different interventions, from top to bottom: control group (no dressing), gauze group, sponge group, and wet adhesive group. Figure b shows the statistical results of blood loss in the rat liver laceration bleeding model after different interventions. Figure c shows the statistical results of hemostasis time in the rat liver laceration bleeding model after different interventions. Wet adhesives exhibit excellent hemostatic properties.
[0033] Figure 10 Antioxidant properties of wet adhesives: Scavenging rate curves of dibenzopicryl radicals in wet adhesives. The wet adhesive exhibits the strongest antioxidant properties when the concentration of introduced polydopamine is 0.4 mg / mL. The antioxidant properties of wet adhesives prepared under different methods increase with increasing concentration.
[0034] Figure 11 Effects of wet adhesives on wound healing: Figure a, from left to right, shows the wound healing status on the day of surgery and on postoperative day 28 in the no-treatment group (control group), cyanoacrylate adhesive group, and wet adhesive group. Figure b shows the HE staining results of wound samples taken from each group on day 28. The multifunctional wet adhesive group showed the best wound healing and the smallest wound width. Detailed Implementation
[0035] The above-described solution will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. All equivalent transformations or modifications made according to the spirit and essence of the invention should be covered within the protection scope of the invention. Implementation conditions not specified in the embodiments are generally conditions found in conventional experiments.
[0036] Example 1: Preparation of a multifunctional wet adhesive
[0037] Dopamine hydrochloride was dispersed in Tris-HCl buffer at pH 8.5 and reacted at 25°C for 60 minutes. The resulting solution was then frozen at -20°C for 24 hours. The frozen ice blocks were then freeze-dried. After 3 days, the moisture in the ice blocks was removed, yielding polydopamine powder. Quaternized chitosan powder was added to a 30% (w / v) acrylic acid solution to construct an acidic and antioxidant solution, with the final concentration of quaternized chitosan being 3% (w / v). After thorough mixing, ammonium persulfate and tetramethylethylenediamine were added to the pre-gel solution to a final concentration of 3% (w / v). After stirring to form a homogeneous solution, the solution was poured into a mold and allowed to stand in a sealed environment for 2 hours to allow the solution to solidify, thus producing a multifunctional wet adhesive.
[0038] Example 2: Preparation of a multifunctional wet adhesive
[0039] Dopamine hydrochloride was dispersed in Tris-HCl buffer at pH 8.5 and reacted at 25°C for 60 minutes. The resulting solution was then frozen at -20°C for 24 hours. The frozen ice blocks were then freeze-dried. After 3 days, the water in the ice blocks was removed, yielding polydopamine powder. Quaternized chitosan powder was added to a 30% (w / v) acrylic acid solution to construct an acidic and antioxidant solution, with a final concentration of 3% (w / v) quaternized chitosan. The prepared polydopamine powder was then added to this solution at a concentration of 0.2 mg / ml. After thorough mixing, ammonium persulfate (3% w / v) and tetramethylethylenediamine (2% v / v) were added to the pre-gel solution. After stirring to form a homogeneous solution, the solution was poured into a mold and allowed to stand in a sealed environment for 2 hours to solidify, thus producing a multifunctional wet adhesive. A schematic diagram of the preparation of the multifunctional wet adhesive is shown below. Figure 1 As shown. The obtained multifunctional wet adhesive is as follows. Figure 2 As shown.
[0040] Example 3: Preparation of a multifunctional wet adhesive
[0041] Dopamine hydrochloride was dispersed in Tris-HCl buffer at pH 8.5 and reacted at 25°C for 60 minutes. The resulting solution was then frozen at -20°C for 24 hours. The frozen ice blocks were then freeze-dried. After 3 days, the moisture in the ice blocks was removed, yielding polydopamine powder. Quaternized chitosan powder was added to a 30% (w / v) acrylic acid solution to construct an acidic and antioxidant solution, with a final concentration of 3% (w / v) quaternized chitosan. The prepared polydopamine powder was then added to this solution at a concentration of 0.4 mg / ml. After thorough mixing, ammonium persulfate (3% w / v) and tetramethylethylenediamine (2% v / v) were added to the pre-gel solution. After stirring to form a homogeneous solution, the solution was poured into a mold and allowed to stand in a sealed environment for 2 hours to solidify, thus producing a multifunctional wet adhesive.
[0042] Example 4: Preparation of a multifunctional wet adhesive
[0043] Dopamine hydrochloride was dispersed in Tris-HCl buffer at pH 8.5 and reacted at 25°C for 60 minutes. The resulting solution was then frozen at -20°C for 24 hours. The frozen ice blocks were then freeze-dried. After 3 days, the moisture in the ice blocks was removed, yielding polydopamine powder. Quaternized chitosan powder was added to a 30% (w / v) acrylic acid solution to construct an acidic and antioxidant solution, with a final concentration of 3% (w / v) quaternized chitosan. The prepared polydopamine powder was then added to this solution at a concentration of 0.8 mg / ml. After thorough mixing, ammonium persulfate (3% w / v) and tetramethylethylenediamine (2% v / v) were added to the pre-gel solution. After stirring to form a homogeneous solution, the solution was poured into a mold and allowed to stand in a sealed environment for 2 hours to solidify, thus producing a multifunctional wet adhesive.
[0044] Example 5: Preparation of a multifunctional wet adhesive
[0045] Dopamine hydrochloride was dispersed in Tris-HCl buffer at pH 8.5 and reacted at 25°C for 60 minutes. The resulting solution was then frozen at -20°C for 24 hours. The frozen ice blocks were then freeze-dried. After 3 days, the moisture in the ice blocks was removed, yielding polydopamine powder. Quaternized chitosan powder was added to a 30% (w / v) acrylic acid solution to construct an acidic and antioxidant solution, with a final concentration of 3% (w / v) quaternized chitosan. The prepared polydopamine powder was then added to this solution at a concentration of 2 mg / ml. After thorough mixing, ammonium persulfate (3% w / v) and tetramethylethylenediamine (2% v / v) were added to the pre-gel solution. After stirring to form a homogeneous solution, the solution was poured into a mold and allowed to stand in a sealed environment for 2 hours to solidify, thus producing a multifunctional wet adhesive.
[0046] Example 6: Physical Properties of Multifunctional Wet Adhesive
[0047] (1) Mechanical strength of multifunctional wet adhesives
[0048] The mechanical strength of the multifunctional wet adhesives in Examples 1 to 5 was determined using a rheometer (MCR302e). To determine the storage modulus G' of the multifunctional wet adhesives, a time-scan test was performed at 37°C with a constant strain of 1% and a frequency of 10 Hz. The results are as follows: Figure 3 As shown.
[0049] The shear-thinning properties of the multifunctional wet adhesive were characterized by measuring linear viscosity in frequency scanning mode. The critical strain point of the multifunctional wet adhesive was determined by strain amplitude scanning tests (γ = 1-1000%). Results are as follows... Figure 4 As shown.
[0050] Furthermore, the storage modulus and loss modulus of the multifunctional wet adhesive were measured in five cycles at 37°C and 1 Hz, using oscillatory strains of 10% and 1000%. The results are as follows... Figure 5 As shown.
[0051] (2) Adhesion strength of multifunctional wet adhesives
[0052] On a general-purpose mechanical testing machine (CMT2103), at 10 mm min... -1 The overlap-shear curves of the multifunctional wet adhesive were tested at a strain rate of [value missing]. To achieve effective adhesion strength analysis, both the multifunctional wet adhesive and fresh pigskin were cut into fixed sizes and shapes. Two pieces of fresh pigskin were joined together using different types of multifunctional wet adhesives. The final adhesion strength test results are shown below. Figure 6 As shown.
[0053] Example 7: Biological effects of multifunctional wet adhesives
[0054] (1) Biocompatibility of multifunctional wet adhesives
[0055] First, 200 mg samples of different multifunctional wet adhesives were treated with ultraviolet light and then co-incubated with complete DMEM medium at 37°C for 24 hours to obtain a conditioned medium for the multifunctional wet adhesives. Then, L929 fibroblasts were cultured at 10 μg / well. 5 Cells were seeded at a density of [number] cells per well in 6-well plates and cultured in conditioned medium at 37°C for 24, 48, and 72 hours. After incubation, the metabolic activity of the cells was determined using the CCK-8 assay. The final biocompatibility test results are as follows: Figure 7 As shown.
[0056] (2) Antibacterial properties of multifunctional wet adhesives
[0057] Bacterial suspensions of Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa with a turbidity of approximately 0.5 were prepared according to McFarland standards. Subsequently, 100 μL of the bacterial suspension was added to 24-well plates. Two groups were selected: a blank control group and the multifunctional wet adhesive prepared in Example 3. After co-culturing with the bacteria for 24 hours, the bacterial suspension was collected and stained with SYTO and propidium iodide (PI). The results are as follows. Figure 8 As shown.
[0058] (3) Hemostatic properties of multifunctional wet adhesives
[0059] Rats were anesthetized by intraperitoneal injection of 50 salbutamol (40 mg / kg). The abdominal fur of the rats was shaved, and the liver was exposed via laparotomy. A 1 cm incision was made on the surface of the liver with a scalpel. Hemostasis was then achieved using gauze, chitosan sponge, or the multifunctional wet adhesive prepared in Example 3. Blood loss and bleeding time before hemostasis were recorded for each group. Results are as follows: Figure 9 As shown.
[0060] (4) Antioxidant properties of multifunctional wet adhesives
[0061] The multifunctional wet adhesive samples prepared in Example 3 were prepared into uniformly sized shapes using a punch. Different multifunctional wet adhesive samples were added to 2 ml of a dibenzopicrylamide free radical solution (0.04 mg / ml) prepared with ethanol. After standing at room temperature for 30 minutes, the mixture was centrifuged (5000 rpm / min, 10 minutes). The supernatant was then collected, and the absorbance was measured at 517 nm. iD3). Detection results are as follows: Figure 10 As shown.
[0062] Example 8: The wound healing effect of a multifunctional wet adhesive
[0063] (1) Animal modeling
[0064] Experimental pigs were anesthetized by intramuscular injection of Serta-50 (3 mg / Kg), and then a 2 cm diameter section of the full-thickness skin was removed from the back of the pigs. 100 μl of Staphylococcus aureus suspension (0.5 McFarland turbidity) was injected into the skin defect site.
[0065] (2) Wound intervention
[0066] Nine experimental pigs, weighing 25–40 kg, were randomly divided into three groups. The modeling process described in Example 8(1) was performed. Subsequently, blank intervention, cyanoacrylate adhesive intervention, and the multifunctional wet adhesive prepared in Example 3 intervention were performed respectively. Medical transparent dressings were applied for protection, and specimens were collected on day 28 for HE staining. Results are shown in […]. Figure 11 The results showed that the multifunctional wet adhesive group exhibited the best wound healing and the smallest wound width.
Claims
1. A method for preparing a multifunctional wet adhesive, characterized in that... Includes the following steps: (1) Dopamine hydrochloride powder was dissolved in Tris-HCl buffer to form a polydopamine solution. The solution was stirred at 20-28°C in a dry environment and then freeze-dried to obtain polydopamine powder. (2) Quaternized chitosan powder is uniformly dispersed in an acrylic acid solution to construct an acidic and antioxidant solution, wherein the final concentration of the quaternized chitosan solution is 1-5% (w / v) and the concentration of acrylic acid is 28-35% (w / v); (3) Disperse the polydopamine powder prepared in step 1 into the solution prepared in step 2, and stir at room temperature for 2-5 hours. The final concentration of the polydopamine solution is 0.2-2 mg / ml. (4) Add ammonium persulfate powder to the solution prepared in step (3), then quickly add tetramethylethylenediamine and N,N'-methylenebisacrylamide, stir vigorously until all components are completely dissolved, stop stirring, seal the solution, and let it stand at room temperature for 2-3 hours to allow the solution to cure naturally into a multifunctional wet adhesive.
2. The method for preparing a multifunctional wet adhesive according to claim 1, characterized in that... Step (1) Dissolve dopamine hydrochloride powder in Tris-HCl buffer at pH 8.5 and stir for 60 minutes at 25°C in a dry environment.
3. The method for preparing a multifunctional wet adhesive according to claim 2, characterized in that... Step (1) The dopamine solution, which has been stirred and dissolved, is frozen in a -20°C freezer for 20-24 hours. Then it is taken out and placed in a freeze dryer for freeze drying. After 3 days, it is taken out to obtain polydopamine powder.
4. The method for preparing a multifunctional wet adhesive according to claim 1, characterized in that... The final concentration of the ammonium persulfate solution formed in step (4) is 2-5% (w / v), and the final concentration of tetramethylethylenediamine is 1-4% (v / v).
5. A multifunctional wet adhesive prepared according to any one of claims 1-4.
6. The use of the multifunctional wet adhesive according to claim 5 in the preparation of products that promote wound healing.
Citation Information
Patent Citations
Preparation method of antibacterial conductive adhesive hydrogel
CN113336893A